A new class of movable (n sub 4) configurations - Berman, Leah (Ars mathematica contemporanea, 2008)
A geometric ?$(n_4)$? configuration is a collection of n points and n lines, usually in the Euclidean plane, so that every point lies on four lines and every line passes through four points. This paper introduces a new class of movable ?$((5m)_4)$? configurations - that is, configurations which admit a continuous family of realizations fixing four points in general position but moving at least one other point - including the smallest known movable ?$(n_4)$? configuration.
Keywords: diskretna geometrija; konfiguracije; matematika